On the Introduction of Psychotechnical Achievements in Law Enforcement Practice - V.M. Pozdnyakov; V.E. Petrov; A.V. Kokurin (Психология и право)
The article is dedicated to examining psychotechnical advancements that are currently utilized or considered promising in modern law enforcement practices. Based on a historical-comparative analysis of scientific approaches and a content analysis of publications from the past five years in domestic journals with a core focus on "Legal Psychology" a classification of traditional and innovative psychotechnical tools has been developed into four specific groups: (1) interactive psychotechnics, (2) organizational-psychological techniques, (3) informational-technical methods and psychotechnics, and (4) analytical psychotechnics. The material of the article highlights the need for further scientific reflection on improving the forms and methods of implementing the achievements of legal psychology in law enforcement activities. The article also outlines prospects for the development of legal psychology in the creation and application of psychotechnical tools.